Bullosis diabeticorum as a differential diagnosis for limb ulcers: case report - Ramos da Silva Grillo, Vinicius Tadeu [UNESP]; Botelho, Mayra Souza [UNESP]; Lange, Eloana Pasqualin [UNESP]; Secanho, Murilo Sgarbi [UNESP]; Bueno de Camargo, Paula Angeleli [UNESP]; Miot, Helio Amante [UNESP] (Soc Brasileira Angiologia Cirurgia Vascular-sbacv, 2022)
Bullosis diabeticorum (BD) is an uncommon cutaneous manifestation of diabetes that can affect the upper limbs. It is characterized by spontaneous and painless non-inflammatory bloody blisters, which can progress to necrosis, requiring differential diagnosis to rule out other dermatological diseases, such as porphyria cutanea tarda, pseudoporphyria, epidermolysis bullosa acquisita, and pemphigoid, and vascular diseases, such as vasculitis, peripheral arterial disease, and Buerger's disease, among others. In this report, we describe a 77-year-old male patient with poorly controlled diabetes and hypertension who presented with spontaneous onset of lesions on the upper limbs, initially with bullous characteristics, progressing to necrotic ulcers after spontaneous rupture. A biopsy revealed hyaline thickening of the dermal vessels and subcorneal bullae, consistent with a diagnosis of BD. After smoking cessation and optimization of glycemia control combined with topical corticosteroid therapy, the condition improved and lesions began to heal. This presentation of BD involving the upper limbs is rare, requiring differential diagnosis to rule out other cutaneous and vascular lesions.
Keywords: bullosis diabeticorum; blister; skin ulcer; diabetes complications; case report